Seed biopriming with P- and K-solubilizing Enterobacter hormaechei sp. improves the early vegetative growth and the P and K uptake of okra (Abelmoschus esculentus) seedling. - Muhamad Aidilfitri Mohamad Roslan; Nurzulaikha Nadiah Zulkifli; Zulfazli M Sobri; Ali Tan Kee Zuan; Sim Choon Cheak; Nor Aini Abdul Rahman (PLoS ONE)
Limited information is available that seed biopriming with plant growth-promoting Enterobacter spp. play a prominent role to enhance vegetative growth of plants. Contrary to Enterobacter cloacae, Enterobacter hormaechei is a less-studied counterpart despite its vast potential in plant growth-promotion mainly through the inorganic phosphorus (P) and potassium (K) solubilization abilities. To this end, 18 locally isolated bacterial pure cultures were screened and three strains showed high P- and K-solubilizing capabilities. Light microscopy, biochemical tests and 16S rRNA gene sequencing revealed that strains 15a1 and 40a were closely related to Enterobacter hormaechei while strain 38 was closely related to Enterobacter cloacae (Accession number: MN294583; MN294585; MN294584). All Enterobacter spp. shared common plant growth-promoting traits, namely nitrogen (N2) fixation, indole-3-acetic acid production and siderophore production. The strains 38 and 40a were able to produce gibberellic acid, while only strain 38 was able to secrete exopolysaccharide on agar. Under in vitro germination assay of okra (Abelmoschus esculentus) seeds, Enterobacter spp. significantly improved overall germination parameters and vigor index (19.6%) of seedlings. The efficacy of root colonization of Enterobacter spp. on the pre-treated seedling root tips was confirmed using Scanning Electron Microscopy (SEM). The pot experiment of bioprimed seeds of okra seedling showed significant improvement of the plant growth (> 28%) which corresponded to the increase of P and K uptakes (> 89%) as compared to the uninoculated control plants. The leaf surface area and the SPAD chlorophyll index of bioprimed plants were increased by up to 29% and 9% respectively. This report revealed that the under-explored species of P- and K-solubilizing Enterobacter hormaechei sp. with multiple plant beneficial traits presents a great potential sustainable approach for enhancement of soil fertility and P and K uptakes of plants.